The Analysis of Romania's External Migration and of the Causality between Remittances and Romania's Economic Growth - Viorica Chirila; Ciprian Chirila (Amfiteatru Economic Journal, 2017)
The Central and East European countries are affected after the fall of the communism, by the international migration for work towards the developed countries. The adherence to the European Union and the lift of restrictions on the labour market in Western Europe facilitated the short-term and definitive emigration. The temporary and definitive departure of a part of the labour force from the emigration countries led to a significant flow of remittances. Being viewed as the main gain of the loss of labour force, remittances are important at macroeconomic level to the extent in which they bring in the receiving country economic growth. The emigration of the labour force may have a positive or a negative influence on the economy of a country according to the way in which remittances received are used by emigrants. This study analyses the impact that the remittances have on the economic development of the country, on investments and exports in Romania. The characteristics of macroeconomic variables used require, for the econometric analysis, the determination of the Granger causality by means of the Toda and Yamamoto's procedure (1995). The results obtained confirm that remittances do not Granger cause either the economic development of Romania expressed in the GDP, or the investments or the exports.
Keywords: F22; F24; C30; 330; remittances; international migration; emigration of labour force; investments; gross domestic product; Granger causality; Romania